Endodontic treatment of a two-rooted mandibular first premolar with four root canals: a case report - Hu, Peiling; Feng, Shuang; Li, Xin; Li, Guangwen; Li, Shiting (Frontiers in Dental Medicine, 2024)
BackgroundMandibular first premolar has a complex and variable anatomy of the root canal system, which often leads to failure of endodontic treatment due to missing root canals. Identifying the complete structure of the root canal system to ensure that all root canals are perfectly cleared and filled becomes critical to the success of root canal therapy. This report introduced a unique case of endodontic treatment of a two-rooted mandibular first premolar in the buccolingual direction with a total of four canals.Case presentationAn adult male patient with a lower left first premolar was diagnosed with acute apical periodontitis and treated with open pulp drainage in a general hospital. One day later, due to the complexity of the root canal structure, the patient was referred to our clinic for subsequent treatment. The tooth #34 was diagnosed with abnormal central cusp, apical periodontitis, and incomplete fracture through clinical and x-ray examinations. Cone-beam Computed Tomography (CBCT) results showed that the tooth #34 processed two roots with a buccolingual bifurcation and a total of 4 root canals: 1 lingual canal, 2 mesiobuccal canals, and 1 distobuccal canal. Notably, the buccal root presented a C-shaped configuration, and the mesiobuccal canals were of 2-1 type. The tooth was treated with microendodontics and crown restoration. One year after the treatment, the follow-up results showed that the tooth #34 was functioning normally without any abnormalities.ConclusionThis report enhances our understanding of the anatomical variations in the root canal system of the mandibular first premolar and emphasizes the importance of CBCT in identifying anatomical variations within the root canal system. Clinicians must be aware of such changes in the mandibular first premolar during treatment to ensure a perfect treatment and better prognosis in clinical practice.